THE EFFECT OF THE SAS (STRUCTURE ANALYSIS SYNTHESIS) METHOD WITH THE HELP OF BACALAH’S BOOK - Lu'lu Nafisah; Muhib Rosyidi (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2023)
Reading is an aspect of language skills that affects students' success in understanding various subjects. Reading Skills, of course, begin with initial reading; preliminary reading is critical so that students have reading skills. This study aims to see and understand the effect of assisted reading books SAS method to improve the ability to read Early Grade II Elementary School students. The technique applied is an experimental method based on the post-test Pretest design of one group with T-test data analysis. The results showed mean pretest = 24.7 and mean posttest = 73.1.  This means there is a significant difference between the initial reading ability of students before treatment and after treatment with the SAS method. The results of the T-test analysis have a significance value of 0.000 which indicates that the significance value 0.05, then Ho is rejected, and Ha is accepted. Therefore, with the help of reading books, the SAS method dramatically affects the early reading ability of Grade II Elementary School students.